Targeted therapy and disease monitoring in CNTRL‐FGFR1‐driven leukaemia. Issue 10 (28th June 2019) - Brown, Lauren M.; Bartolo, Ray C.; Davidson, Nadia M.; Schmidt, Breon; Brooks, Ian; Challis, Jackie; Petrovic, Vida; Khuong‐Quang, Dong‐Anh; Mechinaud, Francoise; Khaw, Seong L.; Majewski, Ian J.; Oshlack, Alicia; et al.
Abstract: We report two patients with leukaemia driven by the rare CNTRL‐FGFR1 fusion oncogene. This fusion arises from a t(8;9)(p12;q33) translocation, and is a rare driver of biphenotypic leukaemia in children. We used RNA sequencing to report novel features of expressed CNTRL‐FGFR1, including CNTRL‐FGFR1 fusion alternative splicing. From this knowledge, we designed and tested a Droplet Digital PCR assay that detects CNTRL‐FGFR1 expression to approximately one cell in 100 000 using fusion breakpoint‐specific primers and probes. We also utilised cell‐line models to show that effective tyrosine kinase inhibitors, which may be included in treatment regimens for this disease, are only those that block FGFR1 phosphorylation.